Nursing of an elderly patient with dermatomyositis complicated by dysphagia and malnutrition (1例老年皮肌炎合并吞咽困难和营养不良患者的护理) - WANG Can (王灿); JIA Xuefei (贾雪飞) (Journal of International Translational Medicine Limited, 2024)
This article summarized the nursing practice of an elderly patient with dermatomyositis complicated by dysphagia and malnutrition. A comprehensive risk assessment on dysphagia and nutritional status was conducted before treatment. A personalized rehabilitation plan consisting of nutrition support, skin care, medication guidance, prevention and treatment of complications and mental health was formulated to relieve the dysphagia symptoms and improve the recovery of the patient. (本文总结1例老年皮肌炎合并吞咽困难和营养不良患者的护理经验。针对患者的吞咽困难以及营养状况及时进行评估, 根据评估结果调整康复方案, 同时加强皮肤护理, 严格规范用药, 积极处理并发症, 并关注患者心理状态, 稳定患者情绪, 改善吞咽障碍, 促进患者早期康复。)